Employment targeting in a frictional labor market. Issue 2 (20th June 2019) - Ghate, Chetan; Mazumder, Debojyoti
Abstract : Purpose: Governments in both developing and developed economies play an active role in labor markets in the form of providing both formal public sector jobs and employment through public workfare programs. The authors refer to this as employment targeting. The purpose of the paper is to consider different labor market effects of employment targeting in a stylized model of a developing economy. In the context of a simple search and matching friction model, the authors show that the propensity for the public sector to target more employment can increase the unemployment rate in the economy and lead to an increase in the size of the informal sector. Design/methodology/approach: The model is an application of a search and matching model of labor market frictions, where agents have heterogeneous abilities. The authors introduce a public sector alongside the private sector in the economy. Wage in the private sector is determined through Nash bargaining, whereas the public sector wage is exogenously fixed. In this setup, the public sector hiring rate influences private sector job creation and hence the overall employment rate of the economy. As an extension, the authors model the informal sector coupled with the other two sectors. This resembles developing economies. Then, the authors check the overall labor market effects of employment targeting through public sector intervention. Findings: In the context of a simple search and matching friction model with heterogeneous agents, the authors show that the propensity for the public sector to target more employment can increase the unemployment rate in the economy and lead to an increase in the size of the informal sector. Employment targeting can, therefore, have perverse effects on labor market outcomes. The authors also find that it is possible that the private sector wage falls as a result of an increase in the public sector hiring rate, which leads to more job creation in the private sector. Originality/value: What is less understood in the literature is the impact of employment targeting on the size of the informal sector in developing economies. The authors fill this gap and show that public sector intervention can have perverse effects on overall job creation and the size of the informal sector. Moreover, a decrease in the private sector wage due to a rise in public sector hiring reverses the consensus findings in the search and matching literature which show that an increase in public sector employment disincentivizes private sector vacancy postings.